HEALTHY LIFESTYLE HYGIENE IN STUDENTS (The New Uzbekistan Journal of Medicine, 2025)
The occurrence of chronic diseases among students and their prevention. The article also provides recommendations on the importance of a healthy lifestyle and ways to apply it in everyday life.